2004
DOI: 10.1086/383130
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Clearance ofPneumocystis cariniiInfection, Increased Inflammation, and Altered Nitric Oxide Metabolism in Lungs of Surfactant Protein–D Knockout Mice

Abstract: Surfactant protein-D (SP-D), a member of the "collectin" family, has been shown to play a role in innate immunity through modulation of inflammation and clearance of organisms. The role of SP-D in host defense against Pneumocystis carinii pneumonia was assessed using SP-D knockout (KO) mice. When inoculated with P. carinii, both wild-type (wt) and SP-D KO mice required CD4 cell depletion to develop infection. In CD4 cell-depleted models, 2 weeks after infection with P. carinii, SP-D KO mice developed increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 57 publications
3
52
2
Order By: Relevance
“…In contrast to increased susceptibility to acute lung injury induced by pathogens (6,45) and bleomycin (17), we found that exposure to 80% oxygen resulted in mortality exclusively in SP-D ϩ/ϩ . As shown in Fig.…”
Section: Sp-dcontrasting
confidence: 80%
See 2 more Smart Citations
“…In contrast to increased susceptibility to acute lung injury induced by pathogens (6,45) and bleomycin (17), we found that exposure to 80% oxygen resulted in mortality exclusively in SP-D ϩ/ϩ . As shown in Fig.…”
Section: Sp-dcontrasting
confidence: 80%
“…In SP-D Ϫ/Ϫ mice, we showed increased susceptibility to bleomycin and evidence of oxidative-nitrative stress (17). Similar findings were observed when the same mice were infected with Pneumocystis carinii (6). Based on the anti-inflammatory properties of SP-D and its association with altered nitric oxide metabolism in both infectious and noninfectious (bleomycin) models of lung injury, we hypothesized that the inflammatory response to pure hyperoxic injury could also be exacerbated by the absence of SP-D. Paradoxically, we found that chronic SP-D deficiency confers resistance to hyperoxia-mediated lung injury.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This protein is a constitutive mediator of Ag clearance and is capable of interacting with cellular components of both the innate and adaptive immune systems on mucosal surfaces (1,2). SP-D is a potent inhibitor of T cell function in vitro (3)(4)(5)(6) and was shown to protect against various inflammatory responses in the lung in vivo (7)(8)(9)(10)(11)(12)(13). SP-D is synthesized and secreted primarily by type II alveolar cells, Clara cells, and cells of submucosal glands in the lung (14), but this collectin can also be found in epithelial surfaces of many other organs (14 -18).…”
mentioning
confidence: 99%
“…In vivo, the use of transgenic mouse models suggests a protective role for SP-D against damage by inflammatory stimuli. Local up-regulation of SP-D protein levels in wild-type mice occurs after a variety of infectious and inflammatory lung injuries, including bacterial and fungal pneumonia, bleomycin, and hyperoxia (12)(13)(14), while mice constitutively deficient in SP-D develop, at baseline, progressive lung inflammation and time-dependent airspace remodeling (15).…”
mentioning
confidence: 99%